Project activity as the way of rising communication effect of senior pupils - N G Sergeeva (Peoples' Friendship University of Russia (RUDN University), 2009)
The article deals with the project activity and its possible influence on communication effect of senior pupils. It determines the conditions of project activity organization raising the communication effect of senior pupils.